EVALUATION OF DROUGHT RESISTANT SAMPLES OF SPRING WHEAT IN THE CONDITIONS OF WEST KAZAKHSTAN REGION - Dzhubatyrova, S.S.; Gubasheva, B.Ye.; Berniyazova, A.M. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
The study drought durum in West-Kazakhstan area has allowed to select the sample, being of interest as source material for breeding on drought. The Studies on revealing the dependencies between size area to sheet surface, drought and productivity within two groups to ripeness have shown that early-ripening sort differ the greater sheet surface, than of the sort. Weakly sample has a smaller sheet surface than high drought sample.
Keywords: drought resistance; sort; wheat; productivity